Predictors of Deviant Behavior Justification among Muslims: Sociodemographic Factors, Subjective Well-Being, and Perceived Religiousness: Array - Nur Amali Aminnuddin; Harris Shah Abd. Hamid (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung in collaboration with Asosiasi Bimbingan dan Konseling Indonesia (ABKIN), 2021)
Current evidence supports how deviant behavior can be predicted by sociodemographic factors, subjective well-being, and perceived religiousness. However, there is limited research when it concerns specificity such as Muslims justifying deviant behavior, and their subjective well-being and perceived religiousness within a single study. Most studies used Christian population or using a non-denominational approach. Therefore, in this study, data from World Value Survey Wave 6 was used to examine the Muslim population (N = 20,559) and deviant behavior justification. Sociodemographic factors, subjective well-being (life satisfaction, happiness, and state of health), and perceived religiousness (prayer frequency and importance of God in life) were hypothesized as predictors. Results revealed that these hypotheses are supported. However, many of these predictors are weak, having minimal effect. This is with the exception of having the worldview of God being important in one’s life, being both a strong and statistically significant predictor of deviant behavior justification. The more a person views God being important in life, the more it predicts a decrease in deviant behavior justification. This research provides a novel finding on the belief-behavior nexus, specifically concerning Muslims justifying deviant behavior when two forms of perceived religiousness—ritualistic and worldview—are being compared.